Proton Pump Inhibitors Do Not Reduce the Risk of Esophageal Adenocarcinoma in Patients with Barrett's Esophagus: A Systematic Review and Meta-Analysis. - Qiang Hu; Tian-Tian Sun; Jie Hong; Jing-Yuan Fang; Hua Xiong; Stephen J Meltzer (PLoS ONE)
Objectives Proton pump inhibitors (PPIs) have been used for treatment of Barrett's esophagus (BE) for many years. However, the connection between PPIs and esophageal adenocarcinoma (EAC) in patients with BE has still been controversial. The current systematic review and meta-analysis was designed to evaluate the association between PPIs and the risk of EAC or high-grade dysplasia (HGD) in patients with BE. Methods A systematic literature search of studies reporting the association between PPIs and the risk of EAC and/or HGD in patients with BE was conducted in PubMed, Embase, Web of Science and the Cochrane Library. Next, literature was screened using previously established criteria and relevant data were extracted from included studies. Finally, the software program Review Manage 5.2 was applied to aggregate data and analyze the results. Results Nine observational studies, comprising five cohort and four case-control studies (including a total of 5712 patients with BE), were identified. Upon meta-analysis, PPIs were found to have no association with the risk of EAC and/or HGD in patients with BE (unadjusted OR 0.43, 95% CI 0.17-1.08). Analysis for duration response relationship revealed no significant trend toward protection against EAC or HGD with PPIs usage for >2~3 years (one study using 7-year cutoff) when compared to usage for shorter time periods (PPIs usage >2~3 years vs. <2~3 years: OR 0.91 (95% CI 0.25-3.31) vs. 0.91 (0.40-2.07)).There also was considerable heterogeneity between studies. Conclusion No dysplasia- or cancer-protective effects of PPIs usage in patients with BE were identified by our analysis. Therefore, we conclude that clinicians who discuss the potential chemopreventive effects of PPIs with their patients, should be aware that such an effect, if exists, has not been proven with statistical significance.